Capacitive and non-capacitive faradaic charge storage. (10th July 2016) - Guan, Li; Yu, Linpo; Chen, George Z.
Abstract: This article aims to offer a critical overview of selected literature on capacitive and non-capacitive faradaic charge storage. It is particularly relevant to the concept of pseudocapacitance that is generally described as a result of fast surfacefaradaic processes. In general, faradaic processes represent electron transfer reactions at the interface between an electrode and its contacting solid or liquid electrolyte phase that is able to accept or donate electrons. Obviously, not all faradaic processes can be associated with pseudocapacitance. The question is how to differentiate pseudocapacitance related faradaic charge storage from the others. Therefore, attempts have been made to apply the band model for semiconductors to account qualitatively for the origin of pseudocapacitance.Capacitive andnon-capacitive faradaic processes are then proposed to define and differentiate different charge storage mechanisms in supercapacitor and battery. On the other hand, the unequal electrode capacitance approach and the use of Ca 2+ in aqueous electrolytes are discussed in relation with enhanced energy capacity of supercapacitors. In addition, the principle of supercapattery as a hybrid device is explained with recent literature examples.